2014
DOI: 10.3402/iee.v4.22110
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of the household and peridomicile and severe dengue: a case–control study in Brazil

Abstract: IntroductionThe potential influence of high-vector-density environments where people are supposedly more exposed to mosquito bites may have a relation to the clinical severity of dengue fever, an association that has been poorly discussed in the literature.ObjectiveThis study aimed at analyzing the association between anthropic environmental factors, particularly those related to the conditions of domicile and peridomicile, and the occurrence of severe dengue cases during the 2008 epidemic in the state of Rio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
5
1
1
Order By: Relevance
“…This might explain the higher risk of dengue for individuals working indoors suggested in the current study. In contrast to other studies [ 61 , 62 ], our results suggested that traveling outside the resident district during the previous three months was negatively associated with dengue risk ( Table 1 ). Studies in Thailand have shown that dengue incidence is commonly spatially clustered [ 63 , 64 ] and infection risk can be highly focal; thus moving out of the study areas might have exposed travelers to differential risks (higher or lower) of dengue transmission.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This might explain the higher risk of dengue for individuals working indoors suggested in the current study. In contrast to other studies [ 61 , 62 ], our results suggested that traveling outside the resident district during the previous three months was negatively associated with dengue risk ( Table 1 ). Studies in Thailand have shown that dengue incidence is commonly spatially clustered [ 63 , 64 ] and infection risk can be highly focal; thus moving out of the study areas might have exposed travelers to differential risks (higher or lower) of dengue transmission.…”
Section: Discussioncontrasting
confidence: 99%
“…Most dengue case-control studies focused on the epidemiological risk factors associated with higher severity of dengue disease, while fewer have investigated the role of entomological factors. Moreover, the majority of those studies used immature Aedes indices to assess the infestation level (density) in the study area [ 61 , 62 ]. Nevertheless, a study in Sao Paulo, Brazil demonstrated a strong association between numbers of female Aedes collected over a fortnight and dengue incidence [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of water reservoirs inside the households results in potential breeding sites and contributes to stable mosquito infestation over time 30,31 . As expected, mosquitoes collection in keysites and daycare facilities were more effective than in the households 30 . In almost all households in which a febrile case dwelt, the Aedes spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were low numbers of DCC, DWS, and DHF, there was a slight increase in the proportion of these cases from 2010. The increase in severe dengue cases may have been associated with the reintroduction of a different serotype 28 .…”
Section: Discussionmentioning
confidence: 99%